Rolul agenției naționale transport auto în prevenirea și combaterea contravenționalității: studiu de caz [Articol] - Pantea, Oleg (CEP USM, 2021)
În articol a fost relevat un studiu de caz privind constatarea faptelor contravenționale de către autoritatea administrativă „Agenția Națională Transport Auto” (ANTA). În context, ne-am referit la două aspecte importante: competența cu privire la constatarea faptelor contravenționale și competența cu privire la examinarea cauzelor contravenționale. La realizarea investigațiilor au fost utilizate materialele oferite de reprezentanții ANTA în cadrul ședințelor organizate de către conducerea instituției, statistica contravențiilor constatate, practica aplicării sancțiunilor contravenționale, formulare de acte procesuale interne ș.a. Totodată, a fost realizată analiza juridică a contravențiilor care sunt de competența ANTA prin prisma elementelor constitutive.

The published material envisages a case study regarding the process of establishing the contraventions by the administrative authority “National Agency of Road Transport” (ANTA). In this context, we referred to two important issues: the competence to establish the contraventions and the competence to examine the contravention cases. When conducting the investigations, the materials provided by the ANTA representatives were used during the meetings organised by the management of the institution, the statistics of the contraventions found, the practice of applying the contravention sanctions, forms of internal procedural acts, etc. We performed a legal analysis of the contraventions that are within the competence of the ANTA through the prism of their constitutive elements.
THE ROLE OF THE NATIONAL AGENCY OF ROAD TRANSPORT IN PREVENTING AND COMBATING CONTRAVENTION: CASE STUDY
Keywords: agent constatator; Agenția Națională Transport Auto; sancțiuni contravenționale; contravention sanctions; constitutive elements; contravention procedure